Selected species of the family Diastylidae (Cumacea, Peracarida, Crustacea) from the deep-sea of the NW Pacific - Mühlenhardt-Siegel, Ute; Lavrenteva, Anna V. (Zootaxa, 2015)
New species of the genera Diastylis, Divacuma and Leptostylis are described. Also a new species of the genus Pseudoleptostyloides, known from the Atlantic, is described for the NW Pacific. Additional information is given on Leptostyloides quadridentata.